2022
DOI: 10.1371/journal.pgph.0000271
|View full text |Cite
|
Sign up to set email alerts
|

Spatial statistical analysis of regional disparities in suicide among policy units in Japan: Using the Bayesian hierarchical model

Abstract: Suicide prevention is a crucial policy issue in Japan to be addressed nationally. Nevertheless, if there are regional differences in suicide, even in adjacent sub-regions, measures may need to be taken at the sub-regional level. Previous studies have not compared regional differences in suicide based on the size of policy units, such as prefectures, secondary medical areas, and municipalities. This study used the number of suicides from open data for 10 years from 2009 to 2018 to obtain shrinkage estimates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The suicide rate in Japan is by far the highest among the Group of Seven industrialized nations, and the leading causes have been reported to include anxiety and depression related to mental stress in the workplace 15 . Despite a modest decrease in the number of suicides after the enactment of the Basic Act on Suicide Prevention by the Japanese Government in 2006, the annual number of suicides remains high at 20,000 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The suicide rate in Japan is by far the highest among the Group of Seven industrialized nations, and the leading causes have been reported to include anxiety and depression related to mental stress in the workplace 15 . Despite a modest decrease in the number of suicides after the enactment of the Basic Act on Suicide Prevention by the Japanese Government in 2006, the annual number of suicides remains high at 20,000 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Japan, characterized by high suicide rates among developed nations, 7 has responded to this issue by enacting the Basic Act for Suicide Prevention 8 . In the general Japanese population, the variability in suicide rates across prefectures has received substantial attention, and widespread research has revealed many suicide‐related factors 9–17 . In contrast, no nationwide research has examined such variations among patients with cancer in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Japanese population, the variability in suicide rates across prefectures has received substantial attention, and widespread research has revealed many suicide-related factors. [9][10][11][12][13][14][15][16][17] In contrast, no nationwide research has examined such variations among patients with cancer in Japan. The Fourth Basic Plan to Promote Cancer Control Programs, proposed by the Ministry of Health, Labour and Welfare of Japan, necessitates tailored measures considering the unique circumstances of each local community.…”
mentioning
confidence: 99%